Analysis of the Effect of GRDP per Capita, Open Unemployment Rate, and Provincial Capital Dummy on Poverty Levels in Regency/City in Java Island in 2023 - Vriska Ayuning Tias; Riswanti Budi Sekaringsih (Bulletin of Islamic Economics, 2025)
Poverty is a fundamental challenge that hinders national progress, negatively affecting social and economic aspects. This study analyzes the effect of Gross Regional Domestic Product (GRDP) per capita, Open Unemployment Rate, and provincial capital status on the poverty rate in regencies/municipalities in Java Island in 2023. Using cross-sectional data from 119 districts/municipalities and the Ordinary Least Squares (OLS) regression method with robust standard errors, it is found that GRDP per capita and provincial capital status have a negative and significant effect on the poverty rate. In contrast, Open Unemployment Rate has a positive and significant effect on the poverty rate. The logarithmic model used shows consistency with economic theory and explains 52.22% of the variation in poverty rates. The findings suggest that inclusive economic growth, job creation, and equitable development outside provincial capitals are essential to reduce poverty in Java.